Analysis of Language Functions in Live Broadcasting Online Seller on TikTok - Yohanna Pebrianti Caroline; Tasya Zahrani; Aulia Nurjannah Sinaga (CV Wahana Publikasi, 2024)
Online seller live broadcasting has become a significant phenomenon in the social media community, especially on platforms like TikTok. Online sellers use specific language and communication strategies to grab users’ attention, promote their products, and drive sales. This research aims to determine the function of language in a live broadcast video of an online seller on TikTok. The qualitative descriptive method was employed to describe each language function observed in the live video broadcasts of online sellers on TikTok. Data collection involved watching and observing the phenomenon of online sellers on the TikTok platform. This process involves several stages. Data analysis: Data reduction is carried out after the data is collected. The research results showed that there are four language functions that online sellers often use on the TikTok media platform: emotive functions, cognitive functions, referential functions, and metalinguistic functions. This language function influences the phenomenon of online sellers on TikTok by providing information about the goods being sold and influencing the audience to buy.